Is gestational weight gain associated with offspring obesity at 36 months?. Issue 4 (30th September 2014) - Diesel, J. C.; Eckhardt, C. L.; Day, N. L.; Brooks, M. M.; Arslanian, S. A.; Bodnar, L. M.
Summary Objective We examined the association between gestational weight gain (GWG) and offspring obesity at age 36 months. Methods Mother–infant dyads (n = 609) were followed from a first study visit (mean [standard deviation]: 18.8 [2.7] weeks gestation) to 36 months postpartum. Total GWG over the entire pregnancy was defined as excessive or non‐excessive according to the 2009 Institute of Medicine guidelines. Four mutually exclusive categories of excessive or non‐excessive GWG across early (conception to first study visit) and late (first study visit to delivery) pregnancy defined GWG pattern. Body mass index (BMI) z‐scores ≥95th percentile of the 2000 Centers for Disease Control (CDC) references defined offspring obesity at 36 months. Multivariable log‐binomial models adjusted for pre‐pregnancy BMI and breastfeeding were used to estimate the association between GWG and childhood obesity risk. Results Nearly half of the women had total excessive GWG. Of these, 46% gained excessively during both early and late pregnancy while 22% gained excessively early and non‐excessively late, and the remaining 32% gained non‐excess weight early and excessively later. Thirteen per cent of all children were obese at 36 months. Excessive total GWG was associated with more than twice the risk of child obesity (adjusted risk ratio [95% confidence interval]: 2.20 [1.35, 3.61]) compared with overall non‐excessive GWG. Compared with a pattern of non‐excessive GWG in both early and late pregnancy, excessive GWG in both periods was associated with an increased risk of obesity (2.39 [1.13, 5.08]). Conclusions Excessive GWG is a potentially modifiable factor that may influence obesity development in early childhood.